Exploring the experience of older people on elder financial exploitation by family members in Malaysia - Che Amani @ Mohd Kamal., Nurfadhilah (2022)
Although elder financial exploitation has gained greater attention in the field of elder abuse research, there are still numerous aspects that have been left unexplored. Currently there is no uniformity in definition of financial exploitation of older persons. The complexity of perceptions regarding what constitutes financial exploitation and similar terms across multiple disciplines and authorities has proved to be an obstacle to identifying financial exploitation in the first place and need of framing and conceptualization. Definitions of financial exploitation and explanation for under reporting and help seeking behaviour is necessary to be explored to gain greater understanding in conceptualization elder financial exploitation. This is done through exploring the views of abused elder victims. This will help the authorities and policy makers in understanding the framing of financial exploitation from the unique perspectives of the victims. It will fill the gap created between the definitions in the literature and lived experience of victims. This study attempted to gain a deep understanding of older Malaysian people’s experience on financial exploitation by family members; explore the barriers that hinder them from disclosing such incidents; how older people deal with such incidents. The study was conducted using phenomenology study design via an in-depth interview of eight older adults who were purposively sampled through purposive and snowball approach. The NVivo 12 analysis software was used to perform and analyse the thematic analysis. Thorough thematic analysis, six major themes were identified to describe the experience of participants with financial exploitation by family members. The participants viewed their financial exploitation experiences as ‘harm’ and ‘exploit’ which is in line with the definition in the literature. The study also discovered how participants felt ‘family comes first’ and ‘helplessness’ as main barriers that hinder them from disclosing the incidents to others. This study also explored various ways on how participants responded to their financial exploitation experiences by ‘seeking assistance’ and ‘non-seeking assistance’. Across interviews, participants also described a range of different ecological factors that influenced how participants shaped their view, barriers that hinder disclosure and help seeking behaviour on financial exploitation experience. Based on older people’s experience, participants shared on individual factors, interpersonal factors which relates to their perpetrators, interpersonal factors which relates to their social networks and institutional and cultural factors that has influence their perception, underreporting and seeking or non-seeking assistance. Based on the findings, this study revealed older people are facing difficult decision to strike a balance between individual rights, interdependence on family and family preservation. Although the participants experience financial exploitation similar to the definition given in the literature, they still face difficulties in detection of abuse incidents especially if they are vulnerable and/ or influenced by cultures and family values. The participants also revealed they received very little social support from within their family, friends, neighbours, and community, which influenced their likelihood of reporting and seeking help. This study contributes to existing knowledge with conceptualization of elder financial exploitation by exploring and comparing definitions and explanations of abuse with the existing literatures. From this study, it is important to explore the conceptualization of elder financial exploitation by family members, to understand the occurrence of financial exploitation and the rationale behind how it influenced reporting and help seeking. This study enabled the understanding and framing of elder financial exploitation by family members by inclusion of victims themselves as research participants. It created a bridge between definitions in the literature and perceptions of victims as there has been limited research in Malaysia on victims’ perception. Finally, this research proposes several recommendations for change in older people’s empowerment, multidisciplinary effort in providing training to professionals as first responders and systemic change within the legal framework in Malaysia.